Pencarian Resep Kue Tradisional berdasarkan Jumlah Likes dan Retweet menggunakan Metode Generalized Vector Space Model - Berlian Bidari Ratna Sari B; Yuita Arum Sari; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Traditional cakes is one diversity form of indonesia. Traditional baking requires a prescription as the basis of material needed to process. Housewives today don't know recipe and how to make traditional cakes who is now drowning by things junk food so they feel lazy to make traditional cakes. Based on the problems that have been described , carried out a search to be the recipe for food in the form of traditional cakes. To get that recipe desirable, the method of Generalized Vector Space Model is needed to determine relevance that recipe desirable. That recipe is in the training having the number of likes and retweet supporting selection a document relevant. Documents recipe used 100 data recipe with 10 types of tradisional cakes. After testing 25 documents, the best Mean Average Preecision was 0.583 using the Generalized Vector Space Model method with weighted likes and retweets. This proves that the search results approach the query entered by the user.